Life Protection and Social Welfare in Pure Sharia Dual-Purpose Life Insurance Products: A Study of the Maqasid Al-Sharia in DSN-MUI Fatwa No. 155/2023 - Muhammad Syafiq Rizqullah; Murjani; khmad Haries; Sunarto (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the application of the Maqasid Syariah principles in Pure Sharia Dual Purpose Life Insurance products based on the DSN-MUI Fatwa No. 155/DSN-MUI/V/2023. The study uses a qualitative approach with an analytical-descriptive research type. The research data consists of primary data in the form of DSN-MUI Fatwa No. 155/2023 and documents on sharia insurance product provisions, while secondary data are obtained from books, scientific journals, and literature related to maqasid sharia and sharia insurance. The data were analyzed using content analysis techniques by examining the suitability of the contract and product management mechanisms to the maqasid sharia principles. The results of the study indicate that the Ta'awun Hibah contract reflects the values ​​of solidarity and mutual assistance between participants, while the Wakalah bil Ujrah and Mudharabah contracts support the principles of transparency and efficiency in fund management. The management of tabarru' funds, the restriction of their use for participant protection, and the allocation of underwriting surplus as a reserve fund demonstrate the application of the principles of hifzh al-mal (asset protection) and the sustainability of Islamic finance. This research confirms that the Pure Sharia Dual Purpose Life Insurance product not only provides financial protection but also supports the values ​​of justice, social welfare, and Sharia-based economic sustainability.